INFLUENCE OF ENVIRONMENTAL PHYSICAL FACTORS ON HUMAN HEALTH - Turdaliyeva Zarina Bahodir qizi; Niyazova Olga Andreevna; G'aniqulova Sevinch Umidjon qizi (American Journals Publishing, 2025)
The article examines the main physical factors of the environment: noise, lighting, vibration, and electromagnetic fields, their effects on the human body, and the role of these factors in shaping favorable or adverse living conditions. An analytical review of modern national and international studies was carried out to assess the influence of these factors on physiological and psychological functions. The approaches of different authors to evaluating permissible exposure levels are compared, and ways to prevent negative impacts are discussed.
Keywords: Physical factors, noise, light, vibration, electromagnetic fields, health, environment, hygiene, living conditions.